The Role of Organization Maturity Level to Improve the Information System Capability - Dantes, Gede Rasben (International Journal of Natural Science and Engineering, 2022)
Organization maturity level is rarely considered when adopted a new technology. Aim of this study is to find the role of organization maturity level in order to improve the information system (IS) capability through ERP implementation approach. There are four variables involved on this study, namely: ERP drives Business Process Reengineering (BPR) (X1), BPR drives ERP (X2) as independent variables, organization maturity level (Y) as a moderating variable, and IS capability (Y1) as a dependent variable. We applied the path analysis to identify direct and indirect effect between ERP implementation approach and IS capability through organization maturity level. There are 277 key individuals from 37 different organization which is represented 10 industrial sectors responded to the questionnaires. The response rate for this survey research is 39.57% from 700 questionnaires which were distributed. Survey result shows that organization maturity level has a major role which can improve to better IS capability in organization. It is shown that a direct effect between X1 and Y1 (ρY1X1=0.331) is lower than an indirect effect between X1 and Y1 through Y (ρYX1 and ρYY1 = 0.369). Whereas, direct effect between X2 and Y1 (ρY1X2=0.096) is lower than indirect effect between X2 and Y1 through Y (ρYX2 and ρYY1 = 0.233). It can be concluded that the organization has to put a more effort on organization maturity level in order to gain a better IS capability, especially when it uses BPR drives ERP approach to implement the ERP system.